Notions of (In)Dependence at a Papua New Guinean University. Issue 2 (20th July 2021) - Syndicus, Ivo
Abstract: This article explores notions of interpersonal dependence and personal independence voiced by university students, graduates, and staff in Papua New Guinea (PNG). It discusses how those obtaining a university education to become regular wage earners reflect on navigating the financial requests of less privileged kin. Wage earners often ascribe dependence to these kin and former sponsors who subsequently may rely on them in times of need. As the number of putatively dependent kin are often large, the process of social stratification that university‐educated wage earners experience also gives rise to reflections about social welfare systems that underlie or could potentially alleviate specific constellations of perceived dependence. Ascriptions of dependence as discussed in this article highlight the combination of the dynamic circumstances of ongoing social stratification and nation‐making with increased levels of connectivity through transport and mobile phone infrastructure, leading an emerging middle class to reconsider some of their social connections.